Schwinger's quantum action principle : from Dirac's formulation through Feynman's path integrals, the Schwinger-Keldysh method, quantum field theory, to source theory /: from Dirac's formulation through Feynman's path integrals, the Schwinger-Keldysh method, quantum field theory, to source theory. (2015) - Milton, K. A
No abstract available